ANALYSIS OF WOMEN PARTICIPATION IN GUNA MELON (Citrullus Vulgaris) OIL EXTRACTION IN KATAGUM ZONE OF BAUCHI STATE, NIGERIA - Muhammad, M.; Hamidu, B.; Yakubu, S.; Dabo, N. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study analysed women’s participation in Guna melon (Citrullus vulgaris) oil extraction in Katagum Zone of Bauchi State, Nigeria. A multi-stage sampling technique was used to select 216 women processors, and data were collected through a structured questionnaire. Descriptive statistics and logit regression were employed to analyse socioeconomic characteristics, participation levels, and determinants of participation. Findings showed that most (97%, 52.3%, 53.2% and 56%) of the respondents were young (20–39 years), married, literate, and engaged in both farming and processing. Participation levels were high, with 66.7% producing Guna and 76.9% relying on manual processing methods. Logit regression revealed that marital status, educational level, years of processing experience, quantity of oil processed, access to raw materials, and market access were positive and significant determinants of participation (P< 0.01). Conversely, age, occupation, type of processing, annual income, time devoted to processing, and access to extension services negative and significant (P<0.01) influenced participation. The study concludes that women play a central role in Guna oil extraction but face constraints related to technology access, labor intensity, and support services. It recommends improved access to modern processing technologies, targeted extension services, market linkage strengthening, and women-focused capacity-building initiatives to enhance productivity and economic empowerment.